Specific inspiratory muscle training in well-trained endurance athletes - Inbar, O.; Weiner, P.; Azgad, Y.; Rotstein, A.; Weinstein, Y. (Medicine & Science in Sports & Exercise, 2000)
Purpose: It has been reported that arterial O2 desaturation occurs during maximal aerobic exercise in elite endurance athletes and that it might be associated with respiratory muscle fatigue and relative hypoventilation. We hypothesized that specific inspiratory muscle training (SIMT) will result in improvement in respiratory muscle function and thereupon in aerobic capacity in well-trained endurance athletes. Methods: Twenty well-trained endurance athletes volunteered to the study and were randomized into two groups: 10 athletes comprised the training group and received SIMT, and 10 athletes were assigned to a control group and received sham training. Inspiratory training was performed using a threshold inspiratory muscle trainer, for 0.5 h·d-1 six times a week for 10 wk. Subjects in the control group received sham training with the same device, but with no resistance. Results: Inspiratory muscle strength (PImax) increased significantly from 142.2 ± 24.8 to 177.2 ± 32.9 cm H2O (P < 0.005) in the training but remained unchanged in the control group. Inspiratory muscle endurance (PmPeak) also increased significantly, from 121.6 ± 13.7 to 154.4 ± 22.1 cm H2O (P < 0.005), in the training group but not in the control group. The improvement in the inspiratory muscle performance in the training group was not associated with improvement in peak V(dot)Emax, V(dot)O2max, breathing reserve (BR), or arterial O2 saturation (%SaO2), measured during or at the peak of the exercise test. Conclusions: It may be concluded that 10 wk of SIMT can increase the inspiratory muscle performance in well-trained athletes. However, this increase was not associated with improvement in aerobic capacity, as determined by V(dot)O2max, or in arterial O2 desaturation during maximal graded exercise challenge. The significance of such results is uncertain and further studies are needed to elucidate the role of respiratory muscle training in the improvement of aerobic-type exercise capacity.